Towards a comparative evaluation of text-based specification formalisms and diagrammatic notations. (25th March 2019) - Moremedi, Kobamelo; Poll, John Andrew Van Der
Specification plays a pivotal role in software engineering to facilitate the development of highly dependable software. Various techniques for specification work have been developed to provide for precise and unambiguous specifications. Z is a formal specification language that is based on a strongly-typed fragment of Zermelo-Fraenkel set theory and first-order logic to provide for provably correct specifications. While diagrammatic specification languages may lack precision, they may, owing to their visual characteristics be a lucrative option for advocates of semi-formal specification techniques. In this research, we investigate the extent to which diagrammatic notations may capture the essence of, e.g., a Z specification. Several diagrammatic notations are considered and combined for this purpose. A case study is employed towards the end to evaluate the utility of the diagrammatic notation developed in this article. Comparisons on the merits of a diagrammatic notation are presented to further determine their feasibility.